A Bargaining Cooperative and Non-cooperative Game Theory in Wireless Sensor Networks - V. Vinoba; S. Sridevi (International Journal of Mathematics And its Applications, 2017)
A Bargaining Cooperation and non-cooperation has been recognized as an important mechanism to enhance connectivity and throughput in multi-hop wireless networks, especially under varying channel conditions. One major problem of cooperation and non-cooperation is t incurs energy and possibly delays costs. To a rational and selfish node these costs are worth incurring only if it receives at least comparable returns in the long term. In light of this, we propose a new incentive mechanism called bandwidth exchange (BE) where a node can delegate a portion of its bandwidth to another node in exchange for relay cooperation and non-cooperation. a n-node wireless network over a fading channel and use a Cooperative and non-cooperative game Nash Bargaining Solution (CANGNBS) mechanism to study the benefits of BE in terms of rate and coverage gains. In this paper we specifically study BE in the simple form of exchanging orthogonal frequency bands to provide incentives for relaying in a wireless network. Other forms of exchanging bandwidth such as delegation of time-slots or using spreading codes of different lengths are also possible. Using a Nash Bargaining framework, we explore the advantage of BE in both static and fading channels.